1973
DOI: 10.1083/jcb.57.2.424
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of Muscle Capillaries to Exogenous Myoglobin

Abstract: Whale skeletal muscle myoglobin (mol wt 17,800 ; molecular dimensions 25 X 34 X 42A) was used as a probe molecule for the pore systems of muscle capillaries . Diaphragms of WistarFurth rats were fixed in situ at intervals up to 4 h after the intravenous injection of the tracer, and myoglobin was localized in the tissue by a peroxidase reaction . Gel filtration of plasma samples proved that myoglobin molecules remained in circulation in native monomeric form . At 30-35 s postinjection, the tracer marked '75% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(73 citation statements)
references
References 76 publications
(85 reference statements)
6
67
0
Order By: Relevance
“…Simionescu et al [17] reported that it takes 45 seconds for small molecules in pulmonary capillaries to move from these blood vessels through pinocytotic vesicles in vascular endothelial cells to the basement membrane [17]. Their findings are consistent with those in our control group ( Figure 6).…”
Section: Discussionsupporting
confidence: 91%
“…Simionescu et al [17] reported that it takes 45 seconds for small molecules in pulmonary capillaries to move from these blood vessels through pinocytotic vesicles in vascular endothelial cells to the basement membrane [17]. Their findings are consistent with those in our control group ( Figure 6).…”
Section: Discussionsupporting
confidence: 91%
“…If one assumes that the average pore size of the bulk glass also reflects the average size of a protein-occupied pore, then one must conclude that glass-encapsulated apoMb inhabits an extremely confined environment; the calculated pore size is approximately 4 nm in all alkylmodified glasses, and the largest dimension of the protein is 4.2 nm from the crystal structure [56,57]. It should be noted that the actual pore size of a wet-aged glass before drying may be much larger than 4 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of macromolecular transport by the vesicular system, first proposed for blood endothelium by Palade (26) and later confirmed by time-dependent tracer studies (13,33), was originally conceived as a simple shuttling of free vesicles between endothelial surfaces, "like diffusion in quanta" (26). Numerous subsequent studies permit some generalizations concerning the nature of such transport.…”
Section: Interendothelial Contactsmentioning
confidence: 99%